2017
DOI: 10.1038/s41598-017-16243-2
|View full text |Cite
|
Sign up to set email alerts
|

Can Niche Modeling and Geometric Morphometrics Document Competitive Exclusion in a Pair of Subterranean Rodents (Genus Ctenomys) with Tiny Parapatric Distributions?

Abstract: Species with similar ecological requirements coexisting in the same geographic region are prone to competitively exclude each other. Alternatively, they may coexist if character displacement acts to change the niche requirements of one or both species. We used two methodological approaches (ecological niche modeling [ENM] and geometric morphometrics) to test two hypotheses: given their behavioral, morphological, and ecological similarities, one species competitively excludes the other; and, character displacem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 85 publications
(114 reference statements)
0
19
0
Order By: Relevance
“…We used geographical coordinates of the species localities (hereafter “occurrences”) and climatic data to model the ecological niche and potential distribution of the long‐tailed mole including 89 occurrences, 77 from our own fieldwork and the rest from previous studies (Kawada et al, ; Motokawa, Wu, & Harada, ) and the Global Biodiversity Information Facility (https://www.gbif.org) (Table S5, Appendix S1). In order to reduce any effect of sampling bias in our modelling analyses (Boria, Olson, Goodman, & Anderson, ), we spatially filtered the species’ occurrences, retaining the maximum number of them that were separated by at least 10 km from other occurrences; this distance has been used in various studies of small non‐volant mammals (Boria et al, ; Kubiak, Gutiérrez, Galiano, Maestri, & Freitas, ; Soley‐Guardia et al, ). To accomplish this task, we used the R package spThin (Aiello‐Lammens, Boria, Radosavljevic, Vilela, & Anderson, ).…”
Section: Methodsmentioning
confidence: 99%
“…We used geographical coordinates of the species localities (hereafter “occurrences”) and climatic data to model the ecological niche and potential distribution of the long‐tailed mole including 89 occurrences, 77 from our own fieldwork and the rest from previous studies (Kawada et al, ; Motokawa, Wu, & Harada, ) and the Global Biodiversity Information Facility (https://www.gbif.org) (Table S5, Appendix S1). In order to reduce any effect of sampling bias in our modelling analyses (Boria, Olson, Goodman, & Anderson, ), we spatially filtered the species’ occurrences, retaining the maximum number of them that were separated by at least 10 km from other occurrences; this distance has been used in various studies of small non‐volant mammals (Boria et al, ; Kubiak, Gutiérrez, Galiano, Maestri, & Freitas, ; Soley‐Guardia et al, ). To accomplish this task, we used the R package spThin (Aiello‐Lammens, Boria, Radosavljevic, Vilela, & Anderson, ).…”
Section: Methodsmentioning
confidence: 99%
“…The results of our work demonstrate unequivocally that, in some cases, species that present extensive chromosome organization, phenotype, evolutionary history, sperm morphology and genetics differences, which are usually associated with reproductive isolation, can generate natural hybrids. Furthermore, a series of findings in the field of ecology demonstrated that these two species present modifications during the occupation of microhabitats 27 and morphological character displacement when in sympatry 48 , revealing that species are capable of recognizing individuals of another species and presenting ecological responses due to competition and yet they come into contact during the reproductive period and produce hybrids. Mitochondrial DNA analyses placed hybrid individuals within both species, thus providing evidence of bidirectional gene flow because females may belong to either species; furthermore, microsatellite analysis revealed that the genetic makeup of the hybrid population was the result of admixture between the two parental species.…”
Section: Conclusion and Prospectsmentioning
confidence: 99%
“…We compared skull morphology among the 5 hybrids, 39 individuals of C. flamarioni and 45 specimens of C. minutus. Specimens of the parental species were taken from both allopatric and sympatric populations (C. flamarioni-22 allopatric and 17 sympatric; C. minutus-24 allopatric and 21 sympatric); these specimens were collected for a recent study 48 and were deposited in the mammal collection of Laboratório de Citogenética e Evolução at Universidade Federal do Rio Grande do Sul. Since sexual dimorphism in skull shape and size is small for C. minutus 74 and was assumed to be negligible, individuals from different sexes were pooled in all analyses.…”
Section: Microsatellite Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…We delimited the area to calibrate and project models by drawing a 2.5° circular buffer around the localities before thinning. Given its extremely limited dispersal ability (Smith 1974), we consider this area as a reasonable hypothesis of the accessible region via dispersal that minimize the inclusion of regions to which this species does not have access to (Barve et al 2011, Kubiak et al 2017.…”
Section: Input Datamentioning
confidence: 99%